Fungsi Pengawasan Budgeting DPRD Kota Bandung Terhadap APBD Tahun 2023 Dalam Perspektif Siyasah Dusturiyyah - Bayu Anggara; Fauzan Ali Rasyid; Ridwan Eko Presetyo (LPPM Institut Pendidikan Nusantara Global, 2025)
This study discusses the budgeting oversight function of the Bandung City Regional People's Representative Council (DPRD) on the 2023 Regional Budget (APBD) from the perspective of siyasah dusturiyyah. The background of the study lies in the suboptimal budget supervision, which affects the effectiveness of regional development. The aim of this research is to analyze the extent to which the Bandung City DPRD carries out its oversight function and how the impacts and obstacles reflect the principles of good governance and the values of siyasah dusturiyyah. Using an empirical juridical approach through interviews and literature study, this research finds that although supervision is carried out through DPRD commissions, challenges such as limited human resources and political dominance continue to hinder its effectiveness. The siyasah dusturiyyah approach offers ethical and spiritual dimensions that strengthen oversight to be more oriented toward public welfare.